(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
Objective: To investigate the prediction ability of the coping strategies in fear of Coronavirus and post-traumatic stress disorder (PTSD) among frontline workers during coronavirus pandemic. Methods: The participants were 408 volunteer frontline workers who filled out online self-report measures of brief coping, fear of coronavirus, and post-traumatic stress disorder. Results: It shows that coping strategies predicted 28.8% of the variance in fear of Coronavirus and 34.6% of the variance in post-traumatic stress disorder. The most prominent coping strategies are substance abuse then religion. Moreover, there are low levels of fear of Coronavirus and post-traumatic stress disorderamong frontline workers during coronavirus pandemic Conclusion: Coping strategies play a vital role in developing fear of coronavirus and post-traumatic stress disorder.